2022
DOI: 10.1213/xaa.0000000000001610
|View full text |Cite
|
Sign up to set email alerts
|

The Retro Superior Costotransverse Ligament Space as a New Target for Ultrasound-Guided Intertransverse Process Block: A Report of 2 Cases

Abstract: An intertransverse process block (ITPB) is a paraspinal thoracic nerve block technique, where the local anesthetic (LA) is injected into the thoracic intertransverse tissue complex posterior to the superior costotransverse ligament (SCTL). Although an ITPB can be ultrasound-guided, it is performed using surrogate bony landmarks without even identifying the SCTL. This report describes a transverse ultrasound imaging technique to identify the retro-SCTL space and perform an ITPB with a retro-SCTL space injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 15 publications
5
28
0
Order By: Relevance
“…A novel multi-injection costotransverse block,4 which has been categorized as the intertransverse process block (ITPB) by a recent international consensus,5 aims to deposit injectate into the retro-SCTL space,6 a potential compartment posterior to the SCTL and anterior to the erector spinae fascia plane. The medial aspect of the retro-SCTL space connects to the thoracic paravertebral space and the intervertebral foramen 6 7. Both the ventral and dorsal rami of the spinal nerve, with the dorsal root ganglion, lie within the medial aspect of the retro-SCTL space,6 7 which may be the anatomic basis for the ITPB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel multi-injection costotransverse block,4 which has been categorized as the intertransverse process block (ITPB) by a recent international consensus,5 aims to deposit injectate into the retro-SCTL space,6 a potential compartment posterior to the SCTL and anterior to the erector spinae fascia plane. The medial aspect of the retro-SCTL space connects to the thoracic paravertebral space and the intervertebral foramen 6 7. Both the ventral and dorsal rami of the spinal nerve, with the dorsal root ganglion, lie within the medial aspect of the retro-SCTL space,6 7 which may be the anatomic basis for the ITPB.…”
Section: Introductionmentioning
confidence: 99%
“…The medial aspect of the retro-SCTL space connects to the thoracic paravertebral space and the intervertebral foramen 6 7. Both the ventral and dorsal rami of the spinal nerve, with the dorsal root ganglion, lie within the medial aspect of the retro-SCTL space,6 7 which may be the anatomic basis for the ITPB. Dye injection into the retro-SCTL space in cadavers commonly showed anterior spread to the thoracic paravertebral space and posterior spread to the back muscles, whereas medial spread to the epidural space rarely 4 8–10.…”
Section: Introductionmentioning
confidence: 99%
“…Cadaveric evidence4 7 has shown dissemination of injectate deposited within the ITTC into the TPVS. Pleural displacement is often perceived as a proxy marker for correct block application in thoracic paravertebral block studies18; however, evidence in regard to ITP blocks is sparse 19. Block applications in the current trial displayed slight anteriorly pleural displacement and thus seemingly confirmed the anatomical pathway in real-time although it did not substantiate any clinical efficacy.…”
Section: Discussionmentioning
confidence: 53%
“…Evidence of the in vivo ITP block efficacy with regard to sensory blockade is sparse, ambiguous yet evolving and with present generalizability ranging from null to vague. Nevertheless, unilateral ITP blocks are most commonly described as resulting in ipsilateral sensory blockades; however, bilateral blockade is also described 19. The latter may indicate a likely epidural spread but reasons remain unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…We understand the confusion and believe that there is a need for clarification on what is an important update on the thoracic paravertebral anatomy 3–5. Readers are advised to refer to the article by Cho et al 3 in which they used three-dimensional (3D) micro-CT imaging to study the anatomy of the thoracic paravertebral region in undisturbed (undissected) cadaver anatomic specimen blocks 3.…”
mentioning
confidence: 99%